Bone Defect Model Dependent Optimal Pore Sizes of 3D‐Plotted Beta‐Tricalcium Phosphate Scaffolds for Bone Regeneration. Issue 11 (15th May 2019) - Diao, Jingjing; Ding, Huanwen; Huang, Minqiang; Fu, Xiaoling; Zou, Fen; Li, Tianjie; Zhao, Naru; Mao, Chuanbin; Wang, Yingjun
Abstract: Bones such as long bone and flat bone vary physiologically and anatomically. How pore sizes affect bone regeneration in different bone defects and its mechanisms are not well studied. Herein, typical long bone (tibia) defect model and flat bone (calvarial) defect model are applied to investigate their bone regeneration capacity and the underlying mechanism mediated by the pore sizes. Pore sizes (100, 250, and 400 µm) of the beta‐tricalcium phosphate (β‐TCP) scaffolds are strictly controlled utilizing a 3D plotting method. Bone regeneration capability in vivo by these pore sizes is related to the defect models (tibial defects and calvarial defects). Among the three pore sizes being studied, 100 µm pore size is most efficient in inducing bone formation in repairing flat bone defects, which is owing to the enhanced osteoblast differentiation in the intramembranous ossification. Differently, the scaffolds with a pore size of 400 µm display the best ability of bone formation for repairing long bone defects, which is speculated to be related to the accelerated formation of cartilage templates and ossification centers in endochondral ossification. This study suggests that bone defect type should be concerned in the design of the porous structure of an artificial material. Abstract : Flat and long bone defect models are used to investigate the effect of pore sizes (100–400 µm) of 3D‐plotted bioceramic scaffolds on their bone regeneration capacity and the underlying mechanisms. A pore size of 100 and 400 µm is found to be the most efficient in inducing bone formation in flat and long bone defects, respectively.